Species and functional diversity of forest communities with wild fruits plants in Central Kazakhstan - Ivanova, Natalya; Shashkov, Maxim (Fundamental and Experimental Biology, 2025)
The alpha, beta, gamma, and functional diversity of forest communities of Central Kazakhstan, which are habitats of wild fruit plants, were analysed. Forest communities were studied in seven sites represented by mountain forests, island forests, and steppe kolki. A total of 41 relevés were collected and analysed. We counted 195 species of vascular plants, including 10 species of fruit plants: Crataegus sanguinea Pall., Lonicera tatarica L., Ribes aciculare Sm., Ribes nigrum L., Ribes saxatile Pall., Rosa acicularis Lindl., Rosa laxa Retz., Rosa majalis Herrm., and Rosa spinosissima L. Results of non-metric multidimensional scaling revealed no dividing of relevés between the studied sites. Cluster analysis using Ward's method identified 4 groups of relevés. No statistically significant differences in alpha diversity scores were found between the groups. Beta-diversity assessment based on Jaccard distance showed that the groups differed well in species composition. The results of functional diversity analysis based on ecological-coenotic groups and calculation of indicator species values showed differences in the structure of the four community groups. It was shown that Rosa majalis is a significant indicator species for the mountain-forest massif of Karkaraly, and Ribes nigrum – for steppe kolki with predominance of forest species. Other fruit species were found in all analysed groups of communities and did not show specific coenotic predilection.